The Extra Length of Stay, Costs, and Mortality Associated With Healthcare‐Associated Infections: A Case‐Control Study - Samaneh Moradi; Zhila Najafpour; Bahman Cheraghian; Iman Keliddar; Razieh Mombeyni (Health Science Reports)
ABSTRACT Background and Aim This study aims to compare the mortality rate, length of stay (LOS), and hospitalization cost in patients with and without healthcare‐associated infections (HCAIs). Methods This prospective cohort study is conducted on 396 matched patients admitted to a tertiary teaching hospital with 800 beds in the southwest of Iran from July 2021 to January 2022. The cases were patients admitted during the study period who had, at minimum, one type of HCAI. For a comparison group, we considered all patients without HCAIs who hospitalized in the same ward and at the same time with the same age and gender in a ratio of one case to three controls. Descriptive analyses were done based on direct medical costs, LOS, and mortality rate in patients. The magnitude of the relationship between potential risk factors and HCAI was quantified using logistic regression. Results The most common HCAI and microorganisms were urinary tract infection (UTI) and Escherichia coli, respectively. The mean LOS for infected patients was 20.3 (±16) days, compared to 8.7 (±8.6) days for noninfected patients (p value ≤ 0.05). Lengths of stay (odds ratio [OR] = 1.09; 95% CI = 1.06–1.19; p value = 0.000), ICU lengths of stay (OR = 1.08; 95% CI = 1.02–1.15; p value = 0.003), presence of central Catheter (OR = 0.127; 95% CI = 0.51–0.319; p value = 0.000), and urinary catheter (OR = 0.225; 95% CI = 0.122–0.415; p value = 0.000), mechanical ventilation (OR = 0.136; 95% CI = 0.57–0.325; p value = 0.000), receipt of immunosuppressors (OR = 1.99; 95% CI = 11.12–3.56; p value = 0.01), were Significantly associated with HCAI. Patients with infections had a more costly hospital stay than noninfected patients (mean diff: $2037.46 ([SD]: 482.25$) (p value = 0.000). The highest cost component was the cost of medication expenditure (mean: $1612.66 ([SD]: $2542.27). Conclusions UTI was the most common HCAI in our study. An infection acquired during a hospital stay may be associated with higher hospitalization costs, prolonged hospitalization, and an increase in the rate of mortality. Longer lengths of stay, presence of central and urinary Catheters, receipt of immunosuppressors, use of mechanical ventilator were common risk factors for HCAI. This study reveals that the median reimbursement cost per hospitalization of patients with HCAIs was higher than patients without HCAIs. This highlights the necessity for implementation of HCAI prevention and control measures.